Evaluation of the approach to hemodialysis vascular access during the pandemic period - (:unkn) unknown (MediHealth Academy, 2022)
Objective: During the pandemic, some surgeries were postponed due to the large number of patients admitted by hospitals. It was tried to shorten the hospitalization period of some patients. Hemodialysis patients who had to come to the hospital frequently were also affected by this situation. Physicians working during the pandemic period prefer to use less invasive techniques. In this study, it was aimed to investigate whether there is a change in the choice of vascular access used for hemodialysis in this period. Material and Method: In this study, 552 patients who were treated for hemodialysis vascular access in the cardiovascular surgery clinic of Kastamonu Training and Research Hospital between March 2019 and 2021 were retrospectively analyzed. The patients were divided into two groups as pre-pandemic (Group 1) and pandemic (Group 2). Patients in Group 1 and Group 2 needed high-flow vascular access to perform hemodialysis. For this purpose, 2 techniques are frequently used, the first being arteriovenous fistula(AVF) and the other permanent hemodialysis catheter insertion. The distribution of these techniques used in patients was examined. Results: In our study, we found that before the pandemic between March 2019-2020, 109 patients had AVF and 193 patients had a permanent tunneled catheter. Between March 2020- 2021, which started with the pandemic process, we found that AVF was opened in 74 patients and a permanent tunnel catheter was placed in 176 patients. Conclusion: Uremic patients who need hemodialysis should not be affected by the pandemic problem and the most permanent procedures should be applied for these patients. Like all vascular patients, dialysis patients should not become secondary afflictions of Covid-19
Keywords: 3. Good health